Perlindungan Hukum Bagi Pasangan Yang Melakukan Perkawinan Beda Agama Di Indonesia - Lu Sudirman; Jendy Herlinda Karwur (Journal of Judicial Review, 2014)
Basically marriage is a human right, but in virtually every human activity continue to be governed by the Act, as well as marriage. In the perspective of human rights, establish a family through marriage is the prerogative of the candidate husband and wife who are already adults. The state's obligation is to protect, record and issue a marriage certificate. But unfortunately, the reality is not sufficiently recognized by the state, even the Law No. 1 Year 1974 on Marriage and KHI no place for interfaith marriage. Clearly then the Law No. 1 of 1974 on Marriage should be revised again. Interfaith marriage are still carried out will have an impact in the future, such as the impact of the marriage's children, children who were born just to have a relationship with his mother alone. Interfaith marriage is not pekawinan mix in terms of our national laws because of mixed marriages under the Act referred to marriage as a marriage that occurred between citizen with foreigners.Methodology used in this research is normative juridical law. The data used in this research is secondary data obtained from the literature (library research) and field research (field research) that is, by interview with the speaker, Mr Cahyono, SH., MH Judges Batam, Mr. Jamaris Head .Dinas population and civil registries, Mr. Badrianus, SH., MH located in the city of Batam Religious Court, and Mr H.Hamizar, M.Sy as head KUA (Office of Religious Affairs) in Batam. Once all the data is collected, then processed and analyzed to find legal issues become the object of study and conclude, then described descriptively.These results indicate that one way in which the interfaith couples is by way of submission to one religion, where one of the parties to follow the religion of his or her spouse. Which is then recorded in accordance with their religious beliefs, to Islam at the Office of Religious Affairs and to the non-Muslims in the Civil Registry Office where the dilangsung her marriage.